Analysis and Improvement of Assembly Line: A Case Study at Automobile Rear-Axle Assembly Line-A PT. ZYX - Prasti Amanda Larasari; Prianggada Indra Tanaya; Yuki Indrayadi (Jurnal Ilmiah Teknik Industri, 2020)
This paper explains the improvement of PT ZYX's productivity on the assembly line-A, using the production line balancing method. Four methods of line balancing were examined, namely, Ranking Positional Weight (RPW), Region Approach, J-Wagon and Kaizen. The selection of the most suitable method is made based on the reduction of number of workstation and cycle-time. Based on the result. Kaizen method shows better total cycle time, number of workstation, and number of operator required. This result is simulated using the 'Tecnomatix' software with the DES (Discrete Event Simulation) method.